375PWhole-exome sequencing of tumour-only samples reveals the association between somatic alterations and clinical features in pancreatic cancer. (24th November 2019) - Lin, H; Ran, W; Chen, X; Wang, B; Yang, P; Li, Y; Xiao, Y; Wang, X; Li, G; Wang, L; Han, Y; Peng, Y; et al.
Abstract: Background: Perturbations in key driver genes or recurrently somatic mutated genes, as well as altered signaling pathways underlying pancreatic cancer have been largely discovered with the help of massive parallel sequencing. However, to date, the relationships between somatic alterations occurrence and clinical features are still less understood in pancreatic cancer. Methods: Using the genomic DNA from each sample, libraries were constructed by shearing genomic DNA and ligating Illumina paired-end adaptors first, then the constructed libraries were hybridized to Agilent Human All Exon Target Enrichment kit V1. The purified capture products were then amplified to make whole exome libraries. The qualified libraries were subjected to 150 base paired-end sequencing on the Illumina NovaSeq instrument. The Genome Analysis Toolkit (GATK) was used to call variants in the sequencing data. All the statistical analyses were performed using IBM SPSS Statistics version 23.0 software. Results: In this study, a total of 54 pancreatic ductal adenocarcinoma patients were enrolled, and pancreatic tumour samples without matched normal tissues were subjected to whole-exome sequencing. Based on the high-confidence putative somatic genes identified from our tumour-only sequencing, the results revealed alterations in cancer progression- and metastatic-related signaling pathways (i.e., E-cadherin and CDC42 signaling pathways) were predominantly enriched in late-stage (stage III/IV) tumours. Moreover, mutant EHMT1, as well as KRT6C, were significantly associated with tumour stage, while mutant H3F3A, DPY19L2, ABCB5, and ASTN1 were all significantly associated with the degree of tumour differentiation. Conclusions: Together, our data suggest the prevalence of association between somatic alteration at the genomic level and clinical features in pancreatic cancer. Legal entity responsible for the study: The authors. Funding: The National Natural Science Foundation of China. Disclosure: All authors have declared no conflicts of interest.